2018
DOI: 10.1017/s1355617718000358
|View full text |Cite
|
Sign up to set email alerts
|

Poorer Visual Acuity Is Associated with Declines in Cognitive Performance Across Multiple Cognitive Domains: The Maine-Syracuse Longitudinal Study

Abstract: Objectives: Prior studies have found associations between visual acuity (VA) and cognitive function. However, these studies used a limited range of cognitive measures and did not control for cardiovascular disease risk factors (CVD-RFs) and baseline function. The primary objective of this study was to analyze the associations of VA and cognitive performance using a thorough neuropsychological test battery. Methods: This study used community-dwelling sample data across the sixth (2001)(2002)(2003)(2004)(2005)(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…The longitudinal analyses indicated greater decline in the low baseline VA group on vision-dependent neuropsychological tests as well as vision-independent tests in episodic memory, language, and executive functions. This is also consistent with previous longitudinal studies (Anstey et al, 2001;Dearborn et al, 2018;Hong et al, 2016;Lin et al, 2004;Valentijn et al, 2005;Zheng et al, 2018). In the Maine-Syracuse Longitudinal Study (Dearborn et al, 2018), which used a multi-domain neuropsychological test battery, VA predicted 5-year change in verbal episodic memory and verbal working memory, as well as in visuospatial organization.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The longitudinal analyses indicated greater decline in the low baseline VA group on vision-dependent neuropsychological tests as well as vision-independent tests in episodic memory, language, and executive functions. This is also consistent with previous longitudinal studies (Anstey et al, 2001;Dearborn et al, 2018;Hong et al, 2016;Lin et al, 2004;Valentijn et al, 2005;Zheng et al, 2018). In the Maine-Syracuse Longitudinal Study (Dearborn et al, 2018), which used a multi-domain neuropsychological test battery, VA predicted 5-year change in verbal episodic memory and verbal working memory, as well as in visuospatial organization.…”
Section: Discussionsupporting
confidence: 90%
“…However, longitudinal studies are needed to investigate the direction of the association and determine whether visual impairment as a risk factor for subsequent cognitive decline over time. While some longitudinal studies have reported supportive evidence thereof (Dearborn et al, 2018;Valentijn et al, 2005), others reported no associations (Hong et al, 2016). However, most studies were limited by relatively brief follow up periods (≤2 years) (Anstey et al, 2001;Lin et al, 2004) or limited cognitive outcome measures, e.g., composed of a single cognitive screening test (Hong et al, 2016;Lin et al, 2004;Zheng et al, 2018).…”
mentioning
confidence: 99%
“…Findings from the current study may have implications for future epidemiological and interventional research in India. Few prior studies have examined the association between vision and cognitive function across multiple domains [33, 34]. In a cohort from the U.S., Dearborn et al [34] reported that VI was associated with future declines in visuospatial, verbal episodic memory, and executive function domains but not working memory or scanning and tracking.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Few prior studies have examined the association between vision and cognitive function across multiple domains [33, 34]. In a cohort from the U.S., Dearborn et al [34] reported that VI was associated with future declines in visuospatial, verbal episodic memory, and executive function domains but not working memory or scanning and tracking. While that study reported associations over 5 years of follow-up, data were not analyzed to determine whether associations varied based on VI severity.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…1,3,6 A recent systematic review and metanalysis 7 reported that vision impairment is associated with 2.4-fold greater odds of cognitive impairment in existing cross-sectional studies and 1.7-fold greater odds in longitudinal studies. However, the association of vision impairment with specific cognitive domains has not been fully elucidated 8 ; there is a lack of data and consensus in the literature on aging on whether the decline is global, process specific, domain specific, or specific to modality of test administration. A metanalysis 9 examining the association between vision and 4 cognitive domainsattention, executive function, memory, and language-found that vision did not mediate age differences in these functioning domains.…”
Section: Introductionmentioning
confidence: 99%